Evaluation of RAS mutational status through BEAMing assay to monitor disease progression of metastatic colorectal cancer: a case report. Issue 9 (October 2020) - Lastraioli, Elena; Lavacchi, Daniele; Palmieri, Valeria Emma; Castiglione, Francesca; Messerini, Luca; Di Costanzo, Francesco; Antonuzzo, Lorenzo
Abstract : Since the introduction of antiepidermal growth factor receptor (anti-EGFR) monoclonal antibodies (moAbs), the treatment of metastatic colorectal cancer (mCRC) has become crucially dependent on the mutation profile of the tumour over the last two decades. Recently, rechallenge strategy with cetuximab-based chemotherapy has demonstrated to be active in a subgroup of patients whose tumour maintained wild-type RAS and RAF status. In this setting, liquid biopsy may replace tissue sample for the identification of specific subgroups of pretreated patients that may benefit from the reintroduction of anti-EGFR moAbs. In November 2014, a 64-year-old man with IVB stage BRAF, KRAS and NRAS wild-type mCRC was admitted in our hospital. He received FOLFIRI cetuximab as first-line treatment with deep and long-lasting partial response (PR), followed by cetuximab maintenance therapy until January 2016. At the time of disease progression, FOLFIRI cetuximab regimen was reintroduced resulting in stabilization of disease and he continued with capecitabine cetuximab therapy until disease progression in October 2016. Then, the patient consecutively received FOLFOX bevacizumab, TAS-102, regorafenib and FOLFIRI followed by de Gramont maintenance treatment. Finally, he was retreated with FOLFIRI cetuximab with disease progression within 3 months and died in May 2019. During his clinical course, liquid biopsy detected two mutations: one in KRAS Cd.12 and one in NRAS Cd. 61. The longitudinal assessment of RAS status offers considerable advantages in order to avoid side effects and economic costs for ineffective treatment choices. Liquid biopsy could help better monitor the disease and provide molecularly guided treatments.